The first riparian skink (Genus: Sphenomorphus Strauch, 1887) from Peninsular Malaysia and its relationship to other Indochinese and Sundaic species - Sumarli, Alexandra; Grismer, L. Lee; Wood, Perry L., Jr.; Ahmad, Amirrudin B.; Rizal, Syed; Ismail, Lukman H.; Izam, Nur Amalina Mohd; Ahmad, Norhayati; Linkem, Charles W. (Zootaxa, 2016)
Recently discovered populations of skinks of the genus Sphenomorphus from central Peninsular Malaysia represent a new species, S. sungaicolus sp. nov., and the first riparian skink known from Peninsular Malaysia. Morphological analyses of an earlier specimen reported as S. tersus from the Forest Research Institute of Malaysia (FRIM), Selangor indicate that it too is the new riparian species S. sungaicolus sp. nov. Additionally, two specimens from the Tembat Forest Reserve, Hulu Terengganu, Kelantan and another from Ulu Gombak, Selangor have been diagnosed as new the species. The latter specimen remained unidentified in the Bernice Pauahi Bishop Museum, Honolulu, Hawaii since its collection in June 1962. Morphological and molecular analyses demonstrate that S. sungaicolus sp. nov. forms a clade with the Indochinese species S. maculatus, S. indicus, and S. tersus and is the sister species of the latter. Sphenomorphus sungaicolus sp. nov. can be differentiated from all other members of this clade by having a smaller SVL (66.5–89.6 mm); 39–44 midbody scale rows; 72–81 paravertebral scales; 74–86 ventral scales; a primitive plantar scale arrangement; and 20–22 scale rows around the tail at the position of the 10th subcaudal.